Sustainability after COVID-19: pillars for a just transition - Morrissey, John; Heidkamp, Patrick (Environmental Sustainability, 2022)
The vulnerability of the global economy has been starkly exposed by the COVID-19 pandemic. Longer term thinking and new approaches to development and prosperity are urgently required. In this paper, we forward a series of principles on which economic and development policy for the post-COVID era should be developed. These are outlined as five ‘pillars’ from which to rebuild the global economy, based on principles of a shared sustainable prosperity. These pillars are: (I) an ecological prosperity; (II) a decarbonized economy; (III) a shared cost burden; (IV) a governance new deal; (V) a just resilience. In outlining the ‘5 pillars’ we explicitly recognize that sustainability cannot simply be a ‘green’, or environmental concern. Social and economic dimensions of sustainability are key for societal stability and continuity. This is made ever starker in the context of the fundamental economic and societal restructuring forced by the disruption of the COVID-19 pandemic. In this regard, the pillars represent a triple bottom line framing of sustainability, of mutually supportive domains of economic, social and environmental well-being. The five pillars are informed by principles of distributive and procedural justice, recognizing the importance and advantages of real community engagement and empowerment and giving due respect and deference to the ecological carrying capacity of our fragile planet. We argue that the post-COVID-19 re-build represents a once-in-a generation opportunity to markedly shift developed trajectories to more sustainable pathways, to rebalance the domains of sustainability, and in the process, to address longer-term crises including those of climate and biodiversity loss.
Keywords: COVID-19; Climate crisis; Prosperity; Resilience; Social justice; Sustainability; dept.egm; peer-reviewed